الابراكسيا الفمية الوجهية عند المصابين بالامراض الاضمحلالية - بوشيخي, اسمهان; بن زينة, عائشة (My University, 2020)
‌د ملخص الدراسة يشمل موضوع بحثنا حول الأبراكسيا الفمية الوجهية عند الدصابتُ بالامراض الاضمحلالية (باركنسون) ، وىو موضوع خصب و مهم في لرال العلوم العصبية والدعرفية ، حيث أن تأثتَه الواضح على الدصاب لا يقتصرفقط على المجال الحركي لديو و الظا يشمل جميع النشاطات اليومية لديو، بحيث قام بحثنا بفرضية مفادىا مدى تأثر البراكسيا الفمية الوجهية بالأمراض الاضمحلالية(باركنسون) فاستعنا بذلك لعدة اختبارات لدعرفة الجانب الدعرفي والحركي، باختبار الفحص الدختصر للحالة العقلية ل "فولشتتُ" folsteinالذي يقيم الوظائف الدعرفية ولػدد درجة اضطرابها. كما استعملنا اختبار لتقييم الأبراكسيا الفمية الوجهية ، بالاعتماد على منهج دراسة حالة على عينة متكونة من حالة واحدة تعاني من مرض باركنسون لشبو انعدامها، حيث طبقنا كلا الاختبارين على الحالة للحصول على نتائج موضحة في التحليل الكمي و الكيفي والتي تشتَ الذ سرعة التجاوب مع اختبار( )MMSEحيث لد بذد أي صعوبة في التذكر و الاستًجاع لدى الحالة ، ومن ثم اختبار لتقييم الأبراكسيا الفمية الوجهية . و بالتالر تم التحقق من فرضيات العمل من خلال التحليل الكيفي و الكمي لنتائج الاختبار. الكلمات المفتاحية : الأمراض الاضمحلالية، باركنسون،الأبراكسيا الفمية الوجهية Abstract: Our research topic covers facial oral apraxia in people with neurodegenerative diseases les maladies neurodègènèrative (parkinson) ; and It is an important subject in the field of neuroscience and cognitive sciences، as its apparent effect on the injured is not limited only to his locomotor field but rather includes all daily activities he has، so that our research has hypothesized that the extent of oral paraxia is affected by neurodegenerative diseases (parkinson). So we used several tests to find out the cognitive and motor side، with a brief examination of the mental state )Mini Mental State Examination) or (MMSE) of folstein who evaluates cognitive functions and determines the degree of their disorder. We also used a test to evaluate facial oral apraxia (evolution of oral and facial apraxia) of D.Crunelle depending on the methodology of a case study on a sample consisting of one case suffering from Parkinson's disease due to its lack، we applied both tests to the case to obtain the results shown in the quantitative and qualitative analysis، which indicates the speed of response to the MMSE test where she had no difficulty remembering and retrieving the condition، and then a test to evaluate facial oral apraxia. And therefore the working hypotheses were validated by a qualitative and quantitative analysis of the test results. Key Words:degenerative diseases،Parkinson's،Facial Oral Apraxia
Keywords: الابراكسيا الفمية الوجهية،المصاب بمراض الاضمحلالية،باركينسون